Influence of Social Cognitive Cooperation Model with Techniques of Cognitive Restructuring and Engineering Modeling on Self Abasement Students - Diastuti, Ni Putu Nia; Arum MWP, Dewi; Dharsana, I Ketut (Bisma The Journal of Counseling, 2017)
This research is a quasi research ("Quasi Experiment"). The purpose of this research is to know the technique of Cognitive Restructuring in Cognitive Social counseling model influence to Self abasement of class X AP A student, to know Modeling technique in Cognitive Social counseling model influence to Verbal Talent of grade X AP B students, and to know the difference of technique influence Cognitive Restructuring with Modeling techniques in Social Cognitive counseling model on Self Abasement students. The process of collecting data in this study using observation sheet, interview sheet, diary and Self Abasement questionnaire. Data analysis method used is t-test. From this research the technique of Cognitive Restructuring is more influential than the modeling model of Social Cognitive counseling model in improving Self Abasement of the students of class X AP SMK Negeri 1 Singaraja.